Analysis of the Implementation of National Character in Realizing the Learning Achievement of Social Sciences Education Students at Universities in Pekanbaru City - Yogi Riantama Isjoni, Muhammad; Nurdiansyah, Nurdiansyah; Syafriafdi, Non; Akmal, Atqo; Rizka, Mifta; Aliya, Filma (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Character education is the process of providing guidance to students to become complete human beings with character in the dimensions of heart, mind, body,  as well as feelings and intentions. The campus is part of the education system, which is a place for students to learn in terms of knowledge transfer and behavior. Character education is important because it teaches habits of thinking and behavior that help individuals to live and work together as a family, community and nation and helps them make accountable decisions. This research is based on the idea of how to determine the level of responsibility, independence and discipline as part of the national character in realizing the achievements of students majoring in Social Sciences at UNRI (Riau State University) and UIN SUSKA (Sultan Syarif Kasim State Islamic University). This research aims to determine the analysis of national character and to determine the hopes and challenges of social studies education students at state universities throughout Pekanbaru City. The number of samples used in this research was 179 students majoring in social studies education at two universities, namely the University of Riau and the Sultan Syarif Kasim State Islamic University. The data collection method uses a questionnaire. The analysis technique used in this research is a qualitative approach. The results of the research show that the character of discipline is at a score of 83% and then the character of independence gets an average score of 83.9% and then the character of independence gets an average score of 84%. Meanwhile, the never give up attitude received an average score of 83.4%. The research results show that independence gets the highest average score.